Use of new technologies for population awareness in health issues: The case of Aedes Zero app - Pinheiro Bernardi Primo, Paola; Espinosa Barbosa Miranda, Angelica; Cristo Sant´anna, Hugo (Guará Journal, 2017)
On November 12, 2015, the Ministry of Health decreed the emergency situation in public health in Brazil, due to the increase in the number of cases of microcephaly, which was severely affected by the Zika virus, transmitted by the Aedes Aegypti. In view of this scenario, the Aedes Zero Extension Project emerges, whose focus is to create tools that help in the awareness and fight against the vector, besides contributing to the education process of the population. This article describes the creation of a mobile technology education free app about the Aedes Aegypti, in face of this epidemiological emergency in Brazil. The system was developed using the Intel XDK program, and targeted primary and secondary school students and professionals in primary health care. The creation involved a team of students, teachers and technicians in education at the Federal University of Espírito Santo, within an extension project, and the result of an easy-to-use app with short and direct information and System of Notifications that assists the user in taking preventive actions. The use of educational technologies developed from the context of health services is important for people to get interesting in using the app and they act as agents of multiplication of the tool. In the context of education and health promotion, the "Aedes Zero" app fulfills its function of promoting simple, dynamic and accessible forms of information on prevention and control of arboviruses.